Sindrom izgorevanja pri zaposlenih v nujni medicinski pomoči - Kugonič, Nika (Obzornik zdravstvene nege, 2013)
Introduction: Members of the emergency medical assistance team have been recognized as a high-risk group for experiencing adverse health effects of stress caused by a number of intertwined factors. Excessive, prolonged and unrelenting stress can have serious health consequences and may lead to a burnout syndrome. The purpose of this research was to determine the physical, emotional and behavioral signs and symptoms of stress overload leading to a burnout syndrome. Methods: The study included 60 randomly selected males and females working in one of the four emergency medical assistance units in the Republic of Slovenia. An extensive non-standardized questionnaire consisting of 12 questions was used in the study as a data collection instrument. The data gathered were statistically analysed. Results: Results of the study show that the majority (73.4%) of members of the emergency medical assistance team experience chronic stress overload due to the nature and amount of work. The most stressful is the management of emotional reactions to traumatic situations (88.4%) and the lack of staff (86.6%). The most common burnout signs and symptoms are emotional, mental, and physical exhaustion manifested as fatigue, insomnia, frequent headaches, back and shoulder pain, muscle aches and angry feelings. Discussion and conclusion: Despite heavy stress at work, the duration and frequence of physical, emotional and behavioural signs and/or symptoms experienced by the study participants do not indicate the presence of a burnout syndrome. The participants do, however, report of experiencing some warning signs of impending burnout.
Keywords: burnout; čustveni simptomi; emotional symptoms; izgorevanje; medicinske sestre; nujna medicinska pomoč; obremenjenost; physical symptoms; strain; stres; stress; telesni simptomi; zdravstveni tehniki